Recovery of poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate) from Ralstonia eutropha cultures with non‐halogenated solvents. Issue 2 (24th September 2012) - Riedel, Sebastian L.; Brigham, Christopher J.; Budde, Charles F.; Bader, Johannes; Rha, ChoKyun; Stahl, Ulf; Sinskey, Anthony J.
Abstract Reduced downstream costs, together with high purity recovery of polyhydroxyalkanoate (PHA), will accelerate the commercialization of high quality PHA‐based products. In this work, a process was designed for effective recovery of the copolymer poly(hydroxybutyrate‐co‐hydroxyhexanoate) (P(HB‐co‐HHx)) containing high levels of HHx (>15 mol%) from Ralstonia eutropha biomass using non‐halogenated solvents. Several non‐halogenated solvents (methyl isobutyl ketone, methyl ethyl ketone, and butyl acetate and ethyl acetate) were found to effectively dissolve the polymer. Isoamyl alcohol was found to be not suitable for extraction of polymer. All PHA extractions were performed from both dry and wet cells at volumes ranging from 2 mL to 3 L using a PHA to solvent ratio of 2% (w/v). Ethyl acetate showed both high recovery levels and high product purities (up to 99%) when using dry cells as starting material. Recovery from wet cells, however, eliminates a biomass drying step during the downstream process, potentially saving time and cost. When wet cells were used, methyl isobutyl ketone (MIBK) was shown to be the most favorable solvent for PHA recovery. Purities of up to 99% and total recovery yields of up to 84% from wet cells were reached. During polymer recovery with either MIBK or butyl acetate, fractionation of the extracted PHA occurred, based on the HHx content of the polymer. PHA with higher HHx content (17–30 mol%) remained completely in solution, while polymer with a lower HHx content (11–16 mol%) formed a gel‐like phase. All PHA in solution could be precipitated by addition of threefold volumes of n‐hexane or n‐heptane to unfiltered PHA solutions. Effective recycling of the solvents in this system is predicted due to the large differences in the boiling points between solvent and precipitant. Our findings show that two non‐halogenated solvents are good candidates to replace halogenated solvents like chloroform for recovery of high quality PHA. Biotechnol. Bioeng. 2013; 110: 461–470. © 2012 Wiley Periodicals, Inc.